Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Keuangan Perusahaan Sektor Industrial - Yohanes Kevin Lukna; Edya Nashwa Septika; Citra Amelia Parsi; Renny Maisyarah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research investigates how a company's financial performance is affected by good corporate governance. This type of research is quantitative, the variable (GCG) is represented by institutional ownership and independent board of commissioners. Meanwhile, financial performance is represented by return on assets. This study analyzes 67 industrial companies that have been listed on the IDX from 2021-2024. Purposive sampling was used to collect samples, and the data were analyzed using multiple linear regression. The results show that financial performance is partially influenced by institutional ownership and also the independent board of commissioners.